2008
DOI: 10.1038/labinvest.2008.11
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative expression profiling of highly degraded RNA from formalin-fixed, paraffin-embedded breast tumor biopsies by oligonucleotide microarrays

Abstract: Microarray-based gene expression profiling is well suited for parallel quantitative analysis of large numbers of RNAs, but its application to cancer biopsies, particularly formalin-fixed, paraffin-embedded (FFPE) archived tissues, is limited by the poor quality of the RNA recovered. This represents a serious drawback, as FFPE tumor tissue banks are available with clinical and prognostic annotations, which could be exploited for molecular profiling studies, provided that reliable analytical technologies are fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
64
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(69 citation statements)
references
References 34 publications
5
64
0
Order By: Relevance
“…These advances include newer formalin-fixed paraffin-embedded tissue extraction protocols, cDNA-mediated annealing, selection, extension and ligation, the addition of random hexamer priming to oligo(dT) priming and newly developed array platforms with redesigned probes. [30][31][32][33][34]57,[67][68][69][70][71][72][73][74][75][76][77][78][79][80][81][82] Although sensitivity is low, high specificity and positive predictive value suggest that transcript detection is reliable from formalin-fixed paraffin-embedded tissue. 33 Although RNA isolation techniques from formalin-fixed paraffin-embedded tissues have improved, problems remain, largely because of the greater fragmented nature of RNA in formalin-fixed paraffin-embedded tissue.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…These advances include newer formalin-fixed paraffin-embedded tissue extraction protocols, cDNA-mediated annealing, selection, extension and ligation, the addition of random hexamer priming to oligo(dT) priming and newly developed array platforms with redesigned probes. [30][31][32][33][34]57,[67][68][69][70][71][72][73][74][75][76][77][78][79][80][81][82] Although sensitivity is low, high specificity and positive predictive value suggest that transcript detection is reliable from formalin-fixed paraffin-embedded tissue. 33 Although RNA isolation techniques from formalin-fixed paraffin-embedded tissues have improved, problems remain, largely because of the greater fragmented nature of RNA in formalin-fixed paraffin-embedded tissue.…”
Section: Discussionmentioning
confidence: 99%
“…33 Although RNA isolation techniques from formalin-fixed paraffin-embedded tissues have improved, problems remain, largely because of the greater fragmented nature of RNA in formalin-fixed paraffin-embedded tissue. 30,32,75,78 Magnitudes of differential expression are often higher in formalin-fixed paraffin-embedded tissue than in fresh frozen samples, because of the increased background noise; this increases the odds of false-positive results. 30,83 Despite these concerns, several studies have shown comparable biological information between genome-wide microarray analysis from matched fresh frozen and formalin-fixed paraffin-embedded tissue.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Conversely, when tumoral hormone receptor mRNA was categorised as negative, immunohistochemical protein staining was evident in at least 1% of tumor cells in 37-39% of cases. This discrepancy could reflect the difficulty capturing short-lived, sensitive to degradation mRNA from FFPE tumor blocks, as well as the different fixation and turnover times of ribonucleic acids in relation to proteins [22,23]. Accumulation of the protein due to aberrant catabolism may also be a factor.…”
Section: Discussionmentioning
confidence: 99%